HUBUNGAN KUALITAS TIDUR DENGAN KONSENTRASI PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS NUSA CENDANA - Paceli, Verena; Telussa, Arley Sadra; Setianingrum, Elisabeth Levina; Nurina, Rr Listyawati (Universitas Nusa Cendana, 2022)
Background: The results of a study by the Centers for Disease Control and Prevention (CDC) in 2014 showed that 35.2% of adults (≥18 years) in the United States had short sleep duration. Medical students are relatively prone to having poor sleep quality. Sleep quality is one of the factors that affect concentration, where poor sleep quality can have an impact on decreased ability to concentrate, memory, ability to solve problems and make decisions and think critically. Objective: To determine the relationship between sleep quality and concentration in students of the Faculty of Medicine, University of Nusa Cendana. Methods: This research is an observational analytic study with cross sectional design conducted on preclinical students of the Faculty of Medicine, University of Nusa Cendana. The sampling technique was stratified random sampling with a sample size of 69 people. Sleep quality data were obtained from filling out the PSQI questionnaire and testing the concentration using the Stroop test. Data analysis used the Contingency coefficient correlation test. Results: The sample with poor sleep quality was 40 people (58%) and 29 people (42%) had good sleep quality. The number of samples with a good concentration was 35 people (50.7%) and a bad concentration was 34 people (49.3%). The results of bivariate analysis using the Contingency coefficient test obtained p value = 0.036 (p <0.05) and r=0,244. Conclusion: There is a significant and weak relationship between sleep quality and concentration among students at the Faculty of Medicine, University of Nusa Cendana. Key words: sleep quality, concentration, medical students.